2013
DOI: 10.1016/j.pec.2013.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Shared decision-making about colorectal cancer screening: A conceptual framework to guide research

Abstract: Objective To develop a conceptual framework to guide research on shared decision-making about colorectal cancer (CRC) screening among persons at average risk and their providers. Methods Based upon a comprehensive review of empirical literature and relevant theories, a conceptual framework was developed that incorporated patient characteristics, cultural beliefs, provider/health care system, health beliefs/stage of adoption, and shared decision-making between patients and providers that may predict behavior.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 110 publications
0
12
0
Order By: Relevance
“…Our study is among the first studies to measure both “informed” and “joint” dimensions of the SDM, as suggested by the USPSTF, between healthcare professionals and patients. Several clinical trials have used the SDM framework to explain the screening decisions on prostate cancer [ 24 , 25 ], colorectal cancer [ 26 ], and breast cancer [ 27 ], but they only focused on the information exchange aspect of the SDM by using the decision aids as an intervention (e.g., educational videotape). In other words, the studies actually measured the concept of informed decision-making instead of the SDM.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is among the first studies to measure both “informed” and “joint” dimensions of the SDM, as suggested by the USPSTF, between healthcare professionals and patients. Several clinical trials have used the SDM framework to explain the screening decisions on prostate cancer [ 24 , 25 ], colorectal cancer [ 26 ], and breast cancer [ 27 ], but they only focused on the information exchange aspect of the SDM by using the decision aids as an intervention (e.g., educational videotape). In other words, the studies actually measured the concept of informed decision-making instead of the SDM.…”
Section: Discussionmentioning
confidence: 99%
“…(23). Tools that facilitate patient preference clarification can help to engage patients and their providers (or agents, such as patient navigators) in shared decision making about screening (24). Systematic reviews have identified few randomized controlled trials of colorectal cancer screening interventions among Hispanics (15,25), and none has used patient preference elicitation and decision support as part of the intervention strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The Health Belief Model is a commonly used framework to explain cancer screening behavior and posits that education and knowledge may modify the pathway between individual perceptions (eg, perceived susceptibility of the disease) and behavior. 33 The clinician plays a key role in patient behavior through advising, communicating, and educating the patient. Clinician-patient interactions regarding preventive services should follow the 5A's: assess, advise, agree, assist, and arrange.…”
Section: Discussionmentioning
confidence: 99%
“…Education for the patient on the benefits, harms, and alternatives for each colorectal cancer screening modality may engage patients in the shared decision making process and increase screening adherence, particularly for race/ ethnic minority patients. 33 Recent evidence suggests that colorectal cancer mortality has increased since 2005 among those aged 40 to 54 years, 35 and in May 2018, the American Cancer Society expanded its colorectal cancer screening recommendations to begin screening at 45 years of age. 36 In our study of patients aged Ն50 years, younger individuals appeared to be at a marginally increased risk of FIT return failure, and although results were not statistically significant, this is consistent with other recent work 13 and troubling in light of trend data.…”
Section: Discussionmentioning
confidence: 99%